2005
DOI: 10.1007/s11149-005-3957-z
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of State-Owned and Privatized Utilities: Ukraine Electricity Distribution Company Performance*

Abstract: Both ownership and regulation affect the behavior of utility managers. Private ownership rewards managerial decisions that enhance shareholder value. Regulatory incentives reward behavior that affects profits and costs. An empirical analysis of 24 Ukraine electricity distribution companies from 1998 to 2002 indicates that privately owned firms do respond to incentives that add to net cash flows (associated with reducing commercial and non-commercial network losses). However, they also respond more aggressively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 28 publications
0
35
0
1
Order By: Relevance
“…The analysis though is restricted to the generation level. Using frontier methods Berg et al (2005) estimate the efficiency of privatized electricity distribution utilities in Ukraine showing that privatized utilities are significantly more efficient. Efficiency measures have also been used by Estache and Rossi (2005).…”
Section: Further Policy Reformsmentioning
confidence: 99%
“…The analysis though is restricted to the generation level. Using frontier methods Berg et al (2005) estimate the efficiency of privatized electricity distribution utilities in Ukraine showing that privatized utilities are significantly more efficient. Efficiency measures have also been used by Estache and Rossi (2005).…”
Section: Further Policy Reformsmentioning
confidence: 99%
“…Thakur et al (2006), for example, reporting on a study of the Indian electricity distribution sector, found evidence that part of its inefficiency is due to the large size of the distribution companies, suggesting that restructuring and downsizing the operations may help utilities to improve their performance. Arocena (2008) Other countries where DEA has been used to evaluate the efficiency of distribution utilities include Norway (Førsund and Kittelsen, 1998;Agrell et al, 2005), Philippines (Pacudan and de Guzman, 2002), Finland (Korhonen and Syrjänen, 2003), Chile (Sanhueza et al, 2004), Colombia (Pombo and Taborda, 2006), Iran (Azadeh et al, 2009a,b), Ukraine (Berg et al, 2005) and Portugal (Weyman-Jones et al, 2004, 2008. It is important to emphasise, however, that whilst some studies exist exploring the use of DEA for the evaluation of electricity distribution utilities in Portugal, they are very rare.…”
Section: Single-country Studiesmentioning
confidence: 99%
“…(1) Network length (km); (2) Total energy net losses (in MWh). Berg, Lin and Tsaplin (2005) 24 electricity distribution companies in Ukraine…”
Section: Modelmentioning
confidence: 99%
“…In addition, a cost function must represent the underlying production (input-output) of the system (e.g., Burns and Weyman-Jones 1996;Filippini and Wild 2001;Berg et al 2005).…”
Section: Average Cost (Norm and Actual)mentioning
confidence: 99%